Resonant metamaterials for contrast enhancement in optical lithography - Dobmann, Sabine; Shyroki, Dzmitry; Banzer, Peter; Erdmann, Andreas; Peschel, Ulf (Optics Express, 2012)
The transmission through ultra-thin metal films is noticeable and thus limits their potential for the formation of lithographic masks. By sub-wavelength patterning of a metal film with a post structure, a resonant metamaterial is formed, which can effectively suppress the transmission. Measurements as well as calculations identify the width of the metal islands as a critical geometrical feature. Hence, the extraordinarily low transmission effect can be explained by the resonant response of single scatterers known as Localized Surface Plasmon Resonances (LSPR). A potential application of this suppressed transmission effect to thin metal masks in optical lithography is experimentally investigated.
EAM Import::2019-03-13